Analisis Pengaruh Lingkungan Kerja dan Motivasi terhadap Kreativitas Karyawan Perum Pegadaian (Kanwil) - Lim Sanny; Raden Ajeng Bebby Cahyani; Yogi Andhika (Bina Nusantara University, 2013)
The purpose of this study is to analyze the effect of work environment and motivation on creativity to Pawnshop employees, Regional Office of Central Jakarta. The method of analysis used in this study is quantitative study with population of 50 Pawnshop employees, Central Jakarta Regional Office. The data were collected by distributing questionnaires consisting of some questions. Variables in this study were divided into 2 groups, working environment (X1) and motivation (X2) as the independent variables, and creativity (Y) as the dependent variable. This research used linear regression analysis method and multiple regressions as tools to solve the problem. Results of the analysis showed that there are significant and simultaneous effects on variables between work environment and motivation on employees’ creativity of the pawnshop, Central Jakarta Regional Office.